Costs associated with rheumatoid arthritis in Italy: past, present, and future - Benucci M; Rogai V; Atzeni F; Hammen V; Sarzi-Puttini P; Migliore A (Dove Medical Press, 2016)
Maurizio Benucci,1 Veronica Rogai,2 Fabiola Atzeni,3 Volker Hammen,4 Piercarlo Sarzti-Puttini,3 Alberto Migliore5 1Rheumatology Unit, S.Giovanni di Dio Hospital, Florence, Italy; 2Eli Lilly Italia SpA, Sesto Fiorentino, Italy; 3Rheumatology Unit, L Sacco Hospital, Milan, Italy; 4Lilly Deutschland GmbH, Bad Homburg, Germany; 5Villa San Pietro Fatebenefratelli Hospital, Rome, Italy Abstract: This literature review examines available evidence on the current and past costs associated with rheumatoid arthritis (RA) in Italy, together with the future health-economic prospects for the disease. Studies have been conducted to date on the prevalence, or the associated costs, of RA in Italy. Although future changes in the incidence of RA are a matter of debate, the impact of RA on health care costs is expected to grow in coming decades in line with projected increases in life expectancy and in the proportion of elderly people in Italy. It has been estimated that the indirect (productivity loss and informal care) and intangible (deterioration in health-related quality of life) costs of the disease will contribute to an increase in national health service expenditure, which will correspond to 1% of the total health care costs of the nation in the near future. The introduction of biological agents for the treatment of rheumatic diseases has resulted in an increase in the direct costs of RA; however, economic analyses that exclude indirect costs will underestimate the full economic impact of RA. The effectiveness of innovative therapies in preventing disease progression and functional impairment may, over time, attenuate the cost impact of RA in terms of hospitalizations and work absenteeism. Further research is needed to develop estimates of the economic impact of different therapeutic approaches in patients with RA in Italy, in order to provide tools that can drive the choice of the most cost-effective therapeutic option while maintaining high-quality care. Keywords: rheumatoid arthritis, prevalence, disease costs, Italy